Plagiarism and Academic Integrity in Indonesian Islamic Higher Education: Factors and Policy Implications - Deddy Ramdhani Deddy; Husnawadi Husnawadi; Waliyadin Waliyadin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
Plagiarism has become a pressing concern in higher education, yet its dynamics within Islamic universities remain largely underexplored. Addressing this gap, the present study investigates the extent of plagiarism among students at an Indonesian State Islamic University and the main factors influencing this academic misconduct. Employing a mixed-methods approach, the study combined survey data with interview evidence to capture both the prevalence and underlying causes of plagiarism. The findings reveal that the overall level of plagiarism among students is relatively high. Among the contributing factors, deficiencies in academic skills emerged as the most prominent, particularly in the ability to paraphrase, synthesize, and properly reference academic work. In addition, the growing familiarity with information and communication technologies (ICT), including artificial intelligence tools, and certain pedagogical practices further facilitated students’ engagement in plagiarism. The convergence of quantitative and qualitative evidence underscores the interplay between limited academic competencies and technological accessibility as key drivers of plagiarism in this context. This study advances the understanding of plagiarism in Islamic higher education by providing empirical evidence from an under-researched region in Indonesia. The findings also carry significant policy implications for the Ministry of Religious Affairs and Islamic universities, highlighting the need for curriculum reforms that integrate academic integrity education, systematic skill training, and the deployment of effective plagiarism- and AI-detection tools. By addressing both structural and pedagogical dimensions, this study contributes to strengthening a culture of academic honesty in Islamic higher education